USING GSM AUTHORIZATION FOR DISTANCE LEARNING SYSTEM - Bychkov, O.C.; Smielov, B.B. (Journal of Information Technologies in Education (ITE), 2010)
In this article describes the structure of the expanded authorization program: an authorization program with feedback;As an feedback,the user is prompted to enter SMS message that was sent by program. In the article discribes the main stages of interaction with the GSM terminal.